The Transformative City: Reflections on the Subject in Two Short Stories by Carmen Naranjo - Solís-Lemus, Valeria (2025)
This article examines the relationship between the city and the subject in two short stories by the Costa Rican writer Carmen Naranjo Coto namely «La invitación» and «Se me lavó la voluntad», both written in the 1960s and published in 1998. For its analysis, particular attention is given to the influence that the space has on the subjects. Thus, the main objective of the study is to analyze the way in which the urban space influences the mood and identity of the subjects represented in the two short stories. To this end, a diverse theoretical base is proposed, which includes literary, philosophical, psychological and sociological postulates. The conclusions of the analysis indicate that the characters created by Naranjo are made invisible and are devoid of everything either because they exclude themselves or because they are excluded from a society that exerts an important force over them.